Urea coated with poultry litter as an option in the control of nitrogen losses Ureia recoberta com cama de aviário como opção no controle de perdas de nitrogênio - Dall'Orsoletta D.J.* (2017)
© 2017, Departamento de Engenharia Agricola - UFCG/Cnpq. All rights reserved.The volatilization of ammonia (NH3) and nitrate leaching (NO3-) are the main processes of nitrogen (N) loss in the soil. The objective of the study was to evaluate N losses by NH3 volatilization and mineral N transformations in the soil with urea coated with poultry litter (urea + litter) compared with other sources of N, under two moisture conditions. The experiment was conducted in a controlled environment with a 5 x 2 factorial arrangement with four replicates, five N sources (urea, SuperN®, Kimcoat®, urea + litter and control without fertilizer) and two moisture contents [80 and 100% of field capacity (FC)]. The total volatilized NH3did not differ between the sources, regardless of the soil moisture condition, ranging from 10.8 to 13.2% of the total N applied. The transformation of NH4+into NO3-did not vary between the sources, except for the control, but it differed between soil moisture contents, with equilibrium estimated at 31 and 38 days, in the treatments with 80 and 100% FC, respectively. The urea + litter has N losses by NH3volatilization and speed of transformation of the soil mineral N similar to those of the other sources, and can be used to substitute them.